Agensi Hayati Jamur Endofit Daun dan Batang Apel Timor - Ernawati Ernawati; Ana Maria Senari; Yoristo Mellu; Milan Boimau (Jurnal Biologi Universitas Andalas, 2023)
ABSTRACTThis study discusses the antimicrobial potential and biological agents of the endophytic fungi on the leaves and stems of Timor apples. Apple plants have been developed in Timor Tengah Selatan (TTS) Regency; however, they slowly stop producing and even die due to disease. Disease control can be done through biological agents with endophytic fungi. This study aims to determine the antimicrobial activity and biological agency of endophytic fungi found in the stems and leaves of the Timor apple plant. This study uses a laboratory experiment method by testing the antimicrobial activity of the isolated endophytic fungi with the well method against E. coli and P. aeruginosa bacteria and C. albicans fungi. Biological agency against pathogenic fungi was tested using antagonist test. The inhibition and antagonist zone data were analyzed descriptively. The study results show that there were three isolates of endophytic fungi, namely IH isolate (black isolate) of Aspergillus sp., IA isolate (bluish green isolate) of Aspergillus sp., and IP isolate (white isolate) of Fusarium sp. Endophytic fungal isolates were found to have activity in inhibiting the growth of the test microbes, with the average inhibition zone of IH of Aspergillus sp. against C. albicans was 15.6 mm, IP of Fusarium sp against P. aeruginosa was 15.9 mm, and IA of Aspergilus sp against E.coli was 11.2 mm. The compound test shows that the endophytic fungal isolates contained alkaloids, terpenoids, and flavonoids. Meanwhile, the antagonist test shows that endophytic fungi were able to inhibit the growth of pathogenic fungi with the growth area coveredthe pathogenic fungus and the widest area was Aspergillus sp.Keywords: antimicrobial, biological agents, endophytic fungi, stems and leaves of Timor apples